Design and Implementation of Raw Milk Reception Dock System - Janardan Chitode, Mr. Samir Phutane, Snehal Jadhav, (International Journal of Scientific Research and Management (IJSRM), 2015)
Agriculture is assured to be the life purpose of the Indian economy along with the animal husbandry. Thus the primary and leading pursuit of farmers has continued to be dairy farming. In last 40 years, the National Dairy Development Board-initiated cooperative movement has quaternated the milk production in India preceding India, the world’s largest milk producing country.The goal of Indian Dairy industry is to handle the national resources so as to increase the milk production and upgrading of processing using various embedded technologies.The proposed system provides the design and implementation of Raw Milk Reception Dock (RMRD).In India, the primary point of liquid milk entry in dairies is Raw Milk Reception Dock (RMRD). It is basically used for the reception of milk and keeping record of incoming milk by tanker